Export Potential Assessment Methodology: The Case of the Republic of Uzbekistan - Sergei S. Sudakov; Alexey A. Zinchenko (Финансовый журнал, 2024)
This paper proposes a universal methodology for assessing export potential of different countries. It takes into account both external and internal supply and demand factors. The methodology is based on the assessment of various trade indices, such as the Balassa index, trade complementarity index and export specialization index. In addition to analyzing the export capabilities of countries, the methodology also focuses on analyzing the countries’ presence in foreign markets (through the geographical structure of imports). The presented methodology is complemented by the estimation of output multipliers (based on Input — Output tables). The calculation of output multipliers takes into account additional induced effects resulting from the growth of household and government incomes, which are partly spent on additional consumption. Complementary analysis of trade indices and output multipliers (including induced effects) allows to identify sectors and products that will most stimulate economic growth by increasing exports. The proposed methodology has been tested on data for the Republic of Uzbekistan in terms of intensive margin of trade. The results of the analysis show that the methodology can be used as a basis for preparing export development programs for individual countries. The methodology could be improved by a deeper analysis of foreign trade barriers, domestic supply factors and extensive trade margins. However, up-to-date information on these improvement factors is not always publicly available.